An efficient data compression and encryption technique for PPG signal. (February 2018) - Dhar, S.; Mukhopadhyay, S.K.; Pal, S.; Mitra, M.
Highlights: A PPG compression and encryption method for efficient storage and transmissions. The algorithm attains attractive CR along with other related numerical identities. An encryption technique is used and encrypted characters are stored in ASCII form. The algorithms do not follow any complex mathematical methods. Abstract: In this paper, a high performing, reliable and robust Photoplethysmogram (PPG) compression and encryption method is proposed for efficient, safe and secure storage and transmission. PPG signals are acquired inside the laboratory using Biopac® data acquisition module and also downloaded from MIMIC database. Digitized PPG samples are passed through an IIR Butterworth Low-pass filter for high frequency noise elimination, down-sampled and then those samples are truncated up to 2nd-decimal places of accuracy. Second difference of those truncated PPG samples (SDPPG) are evaluated and amplified. Amplified integers are grouped using various techniques, encrypted using a symmetric key to convert plain text into cipher text and finally stored in the output file in form of American Standard Code for Information Interchange (ASCII) characters. Since the algorithm is completely reversible, PPG signal is reconstructed using just the reverse algorithm. The algorithm attains an attractive compression performance (Compression Ratio = 122.24, Percent Root Mean Square Difference = 0.02%, Cross Correlation Coefficient = 0.998845, etc.) which is superior to existing PPG compression methods reported to date.